Outsourcing Risk - The Regulation of Occupational Health and Safety Where Subcontractors are Employed - Johnstone, Richard; Mayhew, Claire; Quinlan, Michael (Comparative Labor Law and Policy Journal, 2000)
Disclaimer: This summary was generated by AI based on the content of the source document.